Televizní diskusní pořad o mezietnických vztazích: (Na hraně 26. 4. 1999) - Hašová, Lucie (Lidé města, 2001)
The article is trying, by means of the knowledge from the politeness theory by P. Brown and S. Levinson, to analyse some aspects of the television discussion programme Na hraně (On the Edge), which was devoted to the life of Romanies in the Czech Republic. The author analyses positive and negative politeness strategies of the anchormen and participants in the discussion - representatives of the civil service, politicians, Romany activists and Romany as well as non Romany students. By means of specific example it shows how the individual participants in the programme preserve or threaten their image, how they come to terms with the threat to their image, how they either deliberately threaten the image of other people or preserve and sometimes not only preserve, but also "improve" the image. The analysis has shown that the used strategies largely differed and were socially determined. The initial role, which had been assigned to the participants in the debate, to a large extent influenced the choice of strategy. However, it was also significantly influenced by the experience of individual participants in the performance in a public discussion. This is why the threat and keeping of one's and someone else's image was conducted in various ways and on various levels. The author successively analysed various types of positive and negative politeness strategies. Signs of positive politeness clearly prevailed over the signs of negative politeness. This was caused by the general character of the discussion programme Na hraně, which is not devised to resolve certain problems, but to discuss them and confront the views of the young generation with those of experts. The overwhelming majority of signs of a threat to image (one's own or someone else's), which she found in the programme, was in this or other way connected with the personality of Petr Uhl. Note: This paper was delivered in German at the conference Polyslav, held on October 7-9 in Torun, and a German version will also be published in the proceedings from the conference.